COMPARATIVE ANALYSIS OF EMPLOYEES’ EMPATHY TOWARD PATIENT SATISFACTION BETWEEN STATE-OWNED AND PRIVATE-OWNED PUBLIC HOSPITAL IN MANADO - Nepa, Tesalonika Naomi; Tumbuan, Willem J. F. A. (Universitas Sam Ratulangi, 2019)
Abstract: A patient’s expression of satisfaction or dissatisfaction is a judgment on the quality of hospital care and as an indicator that shall be indispensable to the assessment of the quality of care in hospitals. One assessment of the quality is empathy. The purpose of this study is to compare employees’ empathy toward patient satisfaction between state-owned and private-owned public hospital in Manado. This research is comparative research using quantitative method. The population of this research are the people live in Manado who experienced the service in public hospital in Manado. This research use random sampling technique and the sample of this research are 100 respondents. Data calculated using independent sample t-test and descriptive statistics methods. The result of this study shows there is no significant difference in employees’ empathy toward patient satisfaction between state-owned and private-owned public hospital in Manado. The former patients are dissatisfied with the empathy performance by employees in both hospital. Hospital in Manado should consider about make a training to enhance their employees’ empathy. Keywords: empathy, service, public hospital, patient satisfaction.